Cloud computing adoption framework: Innovation translation approach - Saedi, A. (Institute of Electrical and Electronics Engineers Inc., 2016)
Research on Cloud Computing (CC) adoption seems to be one of the less explored and examined topics in the Information Systems (IS) domains, particularly for Small and Medium-sized Enterprises (SMEs). Prior research on CC adoption does not appreciate the benefits of using Innovation Translation Approach. Instead, Essentialist Approach, a simplistic view of CC adoption which is based only on the technological characteristics of the innovation is prevalent. Thus, this study integrates the Technology-Organization-Environment framework as an IS adoption theory while Actor Network Theory as an Innovation Translation Approach in proposing the SMEs-CC adoption framework. Â© 2016 IEEE.